The magnitude and predictors of therapy abandonment in pediatric central nervous system tumors in low‐ and middle‐income countries: Systematic review and meta‐analysis. Issue 6 (5th March 2019) - Seah, Tiffany; Zhang, Chuer; Halbert, Jay; Prabha, Shashi; Gupta, Sumit
Abstract: Background: Outcomes of pediatric central nervous system (CNS) tumors in low‐ to middle‐income countries (LMIC) are poorer than their high‐income counterparts. Abandonment of therapy is increasingly recognized as a key contributor to this disparity, but has been poorly quantified. We performed a meta‐analysis to determine the magnitude of abandonment in pediatric CNS tumors in LMIC, and risk factors and interventions aimed at reducing this. Patients and methods: We searched seven databases for pediatric CNS tumor cohorts followed up from diagnosis and treated in LMIC. All languages were included. Two reviewers independently selected articles and extracted data on abandonment rates (ARs) and predictors. The authors were contacted for additional information. Results: Of 50 660 publications, 643 in five languages met criteria for full review; 131 met analysis inclusion criteria. ARs were not reported in the majority, and a small number were available from the authors. Available ARs ranged from 0% to 59%, from 38 studies (2497 children in 14 countries), and these were quantitatively analyzed. Lower‐middle‐income countries had higher ARs than upper‐middle‐income countries (27%, 95% confidence interval [CI] 20%–36% vs 9%, 95% CI 6%–14%, P  < 0.0001), with significant heterogeneity within each (LMIC I 2  = 78%, P  < 0.00001, UMIC I 2  = 85%, P  < 0.00001). Common predictors for abandonment included distance to treatment centers, financial hardship, and prognostic misconceptions. Conclusion: In LMICs, ARs are highest in lower‐MICs. However, the paucity of published data limits further evaluation. Given the increasing burden of pediatric CNS tumors in LMIC, addressing deficits in abandonment reporting is critical. Consistent reporting is needed for developing interventions to improve outcomes.